Carrying Sumantra Ghoshal'S Torch: Creating More Positive, Relevant, and Ecologically Valid Research (Academy of Management Journal, 2007)
The article discusses various published reports within the issue, including one by Anita McGahan about research projects that are exciting and another by Freek Vermeulen on conducting relevant research.